Granulomatous response with breast cancer in a developing country: A diagnostic dilemma! - Bushra Siddiqui; Shahbaz Habib Faridi; Veena Maheshwari; Mohammad Aslam; Kafil Akhtar (Iranian Society of Pathology, 2016)
Granulomatous response in association with breast cancer and within the cancer draining lymph nodes is an extremely rare phenomenon. Granulomatous inflammation is an immune response commonly seen against infectious agents and certain non-neoplastic conditions. The etiopathogenesis of granulomas associated with malignancies is not clear but it may be because of an immunologic reaction to tumour antigens. We hereby report a 50-yr-old postmenopausal female presented to Surgical Outpatient Department, Aligarh Muslim University, India, with complaints of lump and pain in her left breast for 6 months. We have also discussed about its etiopathogenesis, final diagnosis, treatment & patient outcome.